Anticipated work-family conflict among STEM students: the role of core self-evaluations and parental role modelling - Brand, Kirsty (School of Management Studies, 2022)
The present study examined the role of core self-evaluations and parental role modelling on STEM students anticipated work-family conflict. Anticipated work-family conflict is the conflict students anticipate experiencing between their work and family roles in the future. Core self-evaluations is an individuals evaluation of themselves or their abilities. Parental role modelling was examined in three forms: parental employment, parental role sharing responsibilities, and perceptions of parental work-family interference. Parental employment refers to whether participants parents were employed full-time, part-time or unemployed during various stages of their careers. Perceptions of parental work-family interference refer to whether participants perceived their parents work interfering with their family or vice versa. Parental role sharing responsibilities is the distribution of work between mother, father or both. A self-report questionnaire was distributed to students at a tertiary institution in South Africa. The data was then recorded and analysed using IBM SPSS Statistics (Version 26). The correlational analysis showed that parental employment and anticipated work-family role planning did not correlate with AWFC. Thus it was expected that both variables would not be predictors of AWFC. The hierarchical regression analysis showed that perceptions of parental work-family interference and core self-evaluations were significant predictors of anticipated work-family conflict. The ANOVA analysis showed no statistically significant differences in anticipated work-family conflict across the categories of maternal employment, paternal employment and parental role sharing responsibilities among STEM students (N = 388). The implications of these findings are discussed, as well as limitations and recommendations for future research.